Manchetes de crimes misóginos na mídia digital brasileira - Alves, Maria Clara Romanini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Brazil is the fifth country that most commits murders of women in the world according to the 2015 map of violence organized by the Latin American Faculty of Social Sciences (FLACSO). At the beginning of 2019 there were 100 cases of femicide (METRÓPOLES, 2019), a fact that proves the persistence of a serious social problem. Furthermore, considering the perspective that we live in a society dominated and exploited by patriarchy, whose project is to remain in that place of power (SAFFIOTI, 2001), the seriousness of the issue is apprehended. Therefore, this work understands the pertinence in understanding this problem from the discursive dimension, focusing on the headlines that were published in the Brazilian digital media regarding misogynist crimes. Based on the conceptual contributions of the Bakhtin Circle about the axiological assessments that constitute the statements, and therefore present ideological values about the figure of the woman, we intend to analyze the misogynistic speech present in headlines. The methodology chosen for this qualitative research was the interpretative and dialogical analysis, in which the collation was used to enable a reflection in relation to the ideology refracted in the headlines. For the selection of the corpus, the factors considered were the theme of the headlines, the socio-historical context in which they were published and the visual elements that accompanied the verbal statement. The results indicate that in all researched digital media, the ideological values present in the headlines come from the patriarchal ideology, which through the choice of words and exposure of the victims 'image, directs the users' reading towards certain ideological values.

O Brasil é o quinto país que mais comete assassinato de mulheres no mundo segundo o mapa da violência de 2015 organizado pela Faculdade Latino-Americana de Ciências Sociais (FLACSO). No início de 2019 ocorreram 100 casos de feminicídio (METRÓPOLES, 2019), fato que comprova a persistência de um grave problema social. Ademais, considerando-se a perspectiva de que vivemos em uma sociedade dominada e explorada pelo patriarcado, cujo projeto é se manter nesse local de poder (SAFFIOTI, 2001), apreende-se a seriedade da questão. Diante disso, este trabalho entende a pertinência em compreender essa problemática a partir da dimensão discursiva, dando enfoque às manchetes que foram publicadas na mídia digital brasileira referentes a crimes misóginos. A partir das contribuições conceituais do Círculo de Bakhtin acerca das avaliações axiológicas que constituem os enunciados, e portanto apresentam valores ideológicos sobre a figura da mulher, pretende-se analisar o discurso misógino presente em manchetes. A metodologia escolhida para essa pesquisa qualitativa foi a de análise interpretativa e dialógica, na qual o cotejo foi usado para viabilizar uma reflexão em relação à ideologia refratada nas manchetes. Para a seleção do corpus, os fatores considerados foram o tema das manchetes, o contexto sócio-histórico em que foram publicadas e os elementos visuais que acompanhavam o enunciado verbal. Os resultados indicam que em todas mídias digitais pesquisadas, os valores ideológicos presentes nas manchetes advém da ideologia patriarcal, que através da escolha de palavras e exposição da imagem das vítimas, direcionam a leitura dos usuários para determinados valores ideológicos.
Headlines of misogynistic crimes in the Brazilian digital media
Keywords: Análise do discurso; Mídia digital; Misoginia